General practitioners' prescribing of lipid‐lowering medications for Indigenous and non‐Indigenous Australians, 2001–2013. Issue 10 (16th November 2015) - Trivedi, Amal N; Pollack, Allan J; Britt, Helena C; Miller, Graeme C; Harrison, Christopher; Kelaher, Margaret A
Abstract: Objective: To examine the prescribing of lipid‐lowering medications during general practitioner encounters with Indigenous and non‐Indigenous Australians from 2001 to 2013. Design, setting and participants: Observational time trend study, using data from the Bettering the Evaluation and Care of Health (BEACH) survey, of 9594 primary care encounters with Indigenous patients and 750 079 encounters with non‐Indigenous patients aged 30 years or over. Main outcome measure: Prescription of at least one lipid‐lowering medication. Results: The age–sex standardised proportion of encounters that resulted in at least one lipid‐lowering medication being prescribed was 5.5% (95% CI, 4.7%–6.3%) for Indigenous patients and 4.6% (95% CI, 4.5%–4.7%) for non‐Indigenous patients. The proportion of encounters with Indigenous patients at which a lipid‐lowering medication was prescribed increased significantly from 4.1% during 2001–2005 to 6.4% during 2009–2013 ( P = 0.013 for trend). For encounters with non‐Indigenous patients, the proportion increased significantly from 3.8% during 2001–2005 to 5.2% during 2009–2013 ( P < 0.01). For encounters during which GPs managed diabetes, hypertension or ischaemic heart disease, the proportion of Indigenous encounters during which lipid‐lowering medication was prescribed was similar to that for non‐Indigenous patients. For encounters in which GPs managed a lipid disorder, however, the age–sex standardised proportion was significantly greater for Indigenous (78.4%; 95% CI, 72.6%–84.2%) than for non‐Indigenous patients (65.2%; 95% CI, 64.5%–65.8%). Conclusion: We detected substantial increases in the prescribing of lipid‐lowering medications from 2001 to 2013 for both Indigenous and non‐Indigenous patients seen in Australian general practice. Providers were more likely to prescribe lipid‐lowering medications for Indigenous than for non‐Indigenous patients, suggesting some measure of success in expanding access to medications and reducing cardiovascular risk among Indigenous people.